A simple peak shifting DSM (demand-side management) strategy for residential water heaters - Atikol, Ugur (Pergamon-Elsevier Science Ltd, 2013)
In many developing countries due to lack of infrastructure the utilities experience difficulties in monitoring their customers' demand or time of use of electricity and hence it is very difficult to apply DSM (demand-side management) programs for peak shifting. In several of these countries the residential EWHs (electric water heaters) are usually responsible for the evening peak. The general attitude of people is to turn them on just before they need hot water and statistics have shown that this takes place in the evening hours constituting the evening peak. The present work reviews the experimental findings about the static and dynamic cooling behavior of hot water in storage tanks and discusses the possible timer programs to avoid the peak hours. It is deduced from the experiments that even when the hot water is kept standing in a tank for 12 h after the initial withdrawal of 64.2 L, it would be possible to have warm water at temperatures above 40 degrees C in the top 15% of the tank to utilize. If the DSM programs are carefully designed it would be possible to set the timers to operate the EWHs for once or twice a day to meet the daily demand of households. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Cyclic load control; Demand-side management; Developing countries; Electrical water heater; Peak shifting